Effect of remdesivir on adverse kidney outcomes in hospitalized patients with COVID-19 and impaired kidney function. - Rituvanthikaa Seethapathy; Qiyu Wang; Sophia Zhao; Ian A Strohbehn; Joshua D Long; James E Dinulos; Destiny Harden; Vinay B Kadiyala; Daiana Moreno; Meghan E Sise (PLoS ONE, 2023)
Background Chronic kidney disease (CKD) is an important risk factor for mortality from COVID-19. Remdesivir has been shown to shorten time to recovery in patients with severe COVID-19. However, exclusion of patients with severe kidney function impairment in clinical trials has led to concerns about kidney safety of remdesivir in patients with pre-existing kidney disease. Methods Retrospective propensity score matched cohort study of hospitalized patients with COVID-19 admitted with estimated glomerular filtration rate (eGFR) between 15 - 60 mL/min/1.73m2. Remdesivir-treated patients were 1:1 matched to historical comparators admitted during the first wave of COVID-19 (between March-April 2020) prior to emergency use authorization of remdesivir using propensity scores accounting for factors predicting treatment assignment. Dependent outcomes included in-hospital peak creatinine, incidence of doubling of creatine, rate of kidney replacement therapy initiation and eGFR among surviving patients at day 90. Results 175 remdesivir-treated patients were 1:1 matched to untreated historical comparators. Mean age was 74.1 (SD 12.8), 56.9% were male, 59% patients were white, and the majority (83.1%) had at least one co-morbidity. There were no statistically significant differences in peak creatinine during hospitalization (2.3mg/dL vs. 2.5 mg/dL, P = 0.34), incidence of doubling of creatinine (10.3% vs. 13.1%, P = 0.48), and rate of kidney replacement therapy initiation (4.6% vs. 6.3%, P = 0.49) in remdesivir-treated patients versus matched untreated historical comparators, respectively. Among surviving patients, there was no difference of the average eGFR at day 90 (54.7 ± 20.0 mL/min/1.73m2 for remdesivir-treated patients vs. 51.7 ± 19.5 mL/min/1.73m2 for untreated comparators, P = 0.41). Conclusions Remdesivir use in patients with impaired kidney function (eGFR between 15 - 60 mL/min/1.73m2) who present to the hospital with COVID-19 is not associated with increased risk of adverse kidney outcomes.